(untitled) (Balneo and PRM Research Journal, 2024)
Introduction: The COVID-19 pandemic has brought significant disruptions to the landscape of oncological medicine, resulting in postponed cancer diagnoses and treatments, suspension of clinical trials, and an overall altered general care. Purpose: This paper aims to evaluate the impact of the COVID-19 pandemic on the profile of patients admitted in a clinical Hospital from Transylvania, and also to evaluate its detrimental effect on the implementation of prehabilitation/rehabilitation programs for patients diagnosed with cancer. Material and methods: The study compared two groups of patients, the ones admitted to the hospital in the year before the pandemic (2019) and the others admitted in 2020. We recorded the number of new cancer diagnoses, the performed interventions of prehabilitation/rehabilitation and we compared the results. Results: A diagnosis of cancer was statistically significantly more frequently established in the pandemic year 2020 compared to the same timeframe of the year 2019. Also, fewer interventions of physical prehabilitation or rehabilitation were applied in the pandemic timeframe. Conclusions: The COVID-19 pandemic had a detrimental effect on the cancer patient´s benefit from prehabilitation/rehabilitation interventions.